2011
DOI: 10.5539/ies.v4n1p78
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Development of Postgraduates’ Research and Supervision

Abstract: Research and supervision have become a vital process in the successful of postgraduate studies. Building an academic career path after Higher National Degree or Bachelor Degree needs intensive training and preparation. This culminates in writing of thesis or dissertation. In this process, the supervisor is designated to facilitate the student's research development based on good resources offered by the institution. At this stage, one of the most common complaints from research students concerns infrequent or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 40 publications
(75 reference statements)
2
60
1
1
Order By: Relevance
“…17 Many graduate degree candidates fail to complete their degrees; in some disciplines, such as the humanities, the number of candidates who fail to complete degrees may exceed 50%. 18 Following good practice may help ensure completion of degrees and make the process manageable and enjoyable. 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Many graduate degree candidates fail to complete their degrees; in some disciplines, such as the humanities, the number of candidates who fail to complete degrees may exceed 50%. 18 Following good practice may help ensure completion of degrees and make the process manageable and enjoyable. 12 …”
Section: Discussionmentioning
confidence: 99%
“…22 It has been found that access to experienced researchers is important to a candidate's success. 18 This creates the dilemma of newly credentialed PhDs having difficulty gaining experience, and experience is a major criterion for good supervision. This problem may be overcome with cosupervision.…”
Section: Choosing Your Candidatementioning
confidence: 99%
“…It carries its significance from the fact that universities are emphasizing on quality research students in order to enhance their own image and rankings (Ismail et al, 2011). Information on the perceptions of students offers very important clues as to what they expect (Lessing & Schulze, 2002).…”
Section: Describe Supervision Asmentioning
confidence: 99%
“…The same identities can be a source of "personal confidence, of resentment, of idealization, of stereotyping, or of dismissiveness" (Grant, 1999, p. 3). The nature of the student-supervisor relationship is potentially influenced by demographic characteristics such as gender and ethnicity (Grant, 1999;Ismail et al, 2011). Kulik and Holbrook (2000) found that service providers' gender and ethnicity affected customers' reactions and acceptability of an unfavorable situation.…”
Section: Previous Research On Supervisor Selectionmentioning
confidence: 99%
See 1 more Smart Citation